Analisis Kritis Penegakan Hukum Pidana terhadap Penyandang Disabilitas dalam Perspektif Keadilan Studi Putusan Mahkamah Agung Nomor 11858 K/PID.SUS/2025 - Mawar Putri Octaviani (Lembaga Yasin AlSys, 2026)
The application of the principle of equality before the law in sexual violence cases involving defendants with disabilities generates a normative dilemma when the demand for maximum protection of victims must be balanced against the fulfillment of the defendant’s constitutional and human rights. This study examines that dilemma in the context of Supreme Court Decision No. 11858 K/PID by highlighting how the criminal justice system harmonizes victim protection under Undang-Undang Nomor 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual with the obligation to respect the rights of persons with disabilities as guaranteed by Article 28D paragraph (1) of UUD 1945 and the Konvensi Hak-Hak Penyandang Disabilitas (UNCRPD), which was ratified through Undang-Undang Nomor 19 Tahun 2011. The study aims to analyze the application of substantive justice and the principle of proportionality in judicial reasoning. A normative legal research method is employed, using conceptual, statutory, and case approaches. The analysis focuses on the ratio decidendi of the decision, the construction of criminal liability, and the consistency of the judges’ arguments with constitutional standards and international obligations. The findings indicate the dominance of a retributive justice paradigm in the increase of the sentence to 12 years’ imprisonment, with victim protection as the primary focus, while the absence of profile assessment and reasonable accommodation for the defendant with disabilities reveals a gap between normative standards and implementation. The study concludes that the application of equality before the law in the a quo case remains formalistic and has not fully realized substantive justice. The implications point to the need for reconstructing a sentencing framework based on proportionality and a disability-inclusive justice approach in order to establish a criminal justice system that is more just, inclusive, and responsive to the rights of both victims and defendants with disabilities.